The emergence and evolution of master terms in the public debate about livestock farming: Semantic fields, communication strategies and policy practices. (October 2019) - Stevens, T.M.; Aarts, N.; Dewulf, A.
Highlights: Loaded terms for contested politicized objects can become powerful framing devices. Loaded terms gain evaluative meaning if consistently used as activist frame. Counter terms and counter frames increase attention and generate a fundamental debate. Master terms not just reflect, but also activate and establish a master frame. Master terms shape conversations and policy practices. Abstract: In the new public space shaped by short, fast, and networked interactions on social media, single keywords, often used in combination with a hashtag, have become important framing devices that structure conversations and communities. This study provides insight into how keywords become dominant framing devices. We conduct a longitudinal comparative case study on the emergence and evolution of two dominant keywords in the Dutch livestock debate: plofkip (booster-broiler) and megastal (mega-stable). Based on an analysis of social media messages, news articles, and policy debates and documents, we study the role of keywords in semantic fields, communication strategies, and policy practices. We present four dynamics that help to understand how keywords become 'master terms': (1) loaded keywords for contested politicized objects can become powerful framing devices because they carry normative meaning and yet are open enough to be applied widely; (2) if activists explicitly and consistently relate the meaning of a loaded term to realities and responsibilities in the sector, the term becomes the signifier of an activist frame; (3) counter terms and frames increase attention, broaden the involvement of actors and deepen the conversation to a value-based debate, through which keywords become master terms; (4) master terms shape policy practices, which in turn reinforces the affordance of the terms in the conversation. We propose the concept of 'master term' as a keyword that not only reflects, but activates and establishes a master frame around which conversations and practices revolve.